The Phenomenon of Farmer Behavior in Using Chemical Pesticides - Ria Widyaningrum (Prospect Publishing, 2023)
Most farmers in Indonesia engage in agricultural activities that use pesticides to control Plant Pests and Diseases (PPD). The use of pesticides by farmers to combat PPDs often disregards the potential environmental impacts. Furthermore, farmers’ limited understanding of environmentally friendly pesticides weakens their awareness of utilizing plant-based pesticides to control PPDs. This phenomenon has resulted in environmental imbalances, which impact the PPD being controlled and the wider ecosystem due to the toxic or poisonous nature of chemical pesticides. Hence, this article aims to explore and comprehend the experiences of farmers who practice agriculture while utilizing chemical pesticides. This study employs a literature review approach by analyzing several articles published between 2008 and 2022 that discuss the topic of pesticide use by farmers in their agricultural activities, including food crops and horticultural plants. The study concludes that farmers' use of chemical pesticides is influenced by various internal and external factors. Encouraging changes in farmers’ behaviour towards the use of environmentally friendly pesticides requires continuous support from local extension agents who provide regular and consistent information to farmers, followed by Integrated Pest Management Field Schools (IPM-FS) activities.